2013
DOI: 10.1589/jpts.25.929
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-term Exercise Training on Cardiorespiratory Fitness of Male Adults with Myocardial Infarction

Abstract: [Purpose] The purpose of this study was to determine the effects of short-term exercise training on the cardiorespiratory fitness (CRF) of individuals suffering from myocardial infarction. [Subjects] A total of 60 participants were divided into experimental (EXP; n=30, mean age 56.7 ± 2.8 years, body mass 80.7 ± 10.7 kg, body height 171.9 ± 7.2 cm) and control (CON; n=30, mean age 56.5 ± 3.1 years, body mass 84.4 ± 12.4 kg, body height 171.5 ± 12.4 cm) groups. [Methods] The members of the EXP group took part i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…It has been reported that accommodation of psychological and physical stressors mainly depends on the activity of the adrenal glands. Bodies under stress need higher rates of metabolic processing along with glucocorticoid release which may affect physical activity 9 , 10 , 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that accommodation of psychological and physical stressors mainly depends on the activity of the adrenal glands. Bodies under stress need higher rates of metabolic processing along with glucocorticoid release which may affect physical activity 9 , 10 , 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic exercises are considered an important component of rehabilitation programs, as they improve the patient’s functional status, and if the intensity of training is adequate, they result in a physiological training effect 19 , 20 , 21 ) .…”
Section: Introductionmentioning
confidence: 99%
“…10 As variáveis que devem ser levadas em consideração para a prescrição de exercício em pacientes que sofreram IAM incluem: intensidade, duração, frequência e modalidade de exercício. 21 Além disso, deve ser dada atenção à intensid de dessa atividade, que tem de ser maior do que as práticas diárias e abaixo do nível que conduz a sintomas clínicos indesejáveis, como a ocorrência de dor ou quando o valor de alguma variável, como frequência cardíaca (FC) e/ou PA, apresentar-se além do desejável para o nível de exercício, sendo este um critério de interrupção das atividades físicas. 22 Conforme as orientações da American Heart Association, 23 recomenda-se pelo menos 30 minutos de exercício em intensidade moderada (60-75% da FC máxima predita) para que se atinjam os benefícios necessários.…”
Section: Discussionunclassified